Monitoring Identification of salt crusts in dry areas by satellite data’s processing - fariba sfanyary; nader sarmasty; sid kazem alavipanah (تحقیقات کاربردی علوم جغرافیایی)
Monitoring the salt crusts in arid areas by satellite data processing in this research, monitoring the salt crusts of KASHAN and MAHARLOO arid areas by using LISSIII datas of IRS-P6 satellite was accomplished. After exerting essential corrections for visual inter pretation , contrast optimization and making pseudo-colorful images were used to specity the salt crusts. Then , according to the salt crusts’ spectral reflections in different bands and spectral rationing, RSCI (ratio salt crust index) and NDSCI (normalized different salt crust index ) were described. The purpose of submitting these indexes is to maximize the differences between spectral reflection and its background in order to make a high quality image for them to be distinctive. finally, by using threshold and error matrix , it was specified that RSCI and NDSCI indexes showed the best separation. The results showed that RSCI and NDSCI indexes are functional for monitoring the salt crusts of arid areas using mutti-spectral satellite data